2018
DOI: 10.1002/jbio.201700219
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free quantitative chemical imaging and classification analysis of adipogenesis using mouse embryonic stem cells

Abstract: Stem cells have received much attention recently for their potential utility in regenerative medicine. The identification of their differentiated progeny often requires complex staining procedures, and is challenging for intermediary stages which are a priori unknown. In this work, the ability of label-free quantitative coherent anti-Stokes Raman scattering (CARS) micro-spectroscopy to identify populations of intermediate cell states during the differentiation of murine embryonic stem cells into adipocytes is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…We have developed an algorithm to analyze CARS hyperspectral images which determines quantitative spectra and absolute concentration images of separate chemical components without prior knowledge, called FSC 3 (factorization into spectra and concentrations of chemical components). , In this method the hyperspectral data are factorized as D = ∑ i C i × S i + E , with C i and S i being the non-negative concentration distribution and spectrum of the i th component, respectively, and E is the error, the norm of which is minimized. This method was recently used to quantitatively measure the lipid uptake in human adipose derived stem cells, , to investigate the differentiation of stem cells, and toward high-throughput imaging using a Bessel beam and sparse sampling . It was also shown to be suited for the quantitative determination of the absolute volume of chemical components in three-dimensional imaging, using polystyrene beads as proof-of-principle .…”
mentioning
confidence: 99%
“…We have developed an algorithm to analyze CARS hyperspectral images which determines quantitative spectra and absolute concentration images of separate chemical components without prior knowledge, called FSC 3 (factorization into spectra and concentrations of chemical components). , In this method the hyperspectral data are factorized as D = ∑ i C i × S i + E , with C i and S i being the non-negative concentration distribution and spectrum of the i th component, respectively, and E is the error, the norm of which is minimized. This method was recently used to quantitatively measure the lipid uptake in human adipose derived stem cells, , to investigate the differentiation of stem cells, and toward high-throughput imaging using a Bessel beam and sparse sampling . It was also shown to be suited for the quantitative determination of the absolute volume of chemical components in three-dimensional imaging, using polystyrene beads as proof-of-principle .…”
mentioning
confidence: 99%
“…This approach allowed us to focus lipid composition analysis exclusively on mature adipocytes and not on the remaining unlipidated stromal component. Previous studies have shown t h e a p p l i c a t i o n o f C o h e r e n t a n t i -S t o k e s R a m a n microspectroscopy to embryonic stem cells undergoing adipogenic differentiation, showing a measure of chemical lipid saturation composition and an increase in LD accumulation with differentiation (71,72). While, very interestingly, individual LDs within one adipocyte appear to have an inhomogeneity in their chemical composition, this was not further analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed us to focus lipid composition analysis exclusively on mature adipocytes and not on the remaining unlipidated stromal component. Previous studies have shown the application of Coherent anti-Stokes Raman microspectroscopy to embryonic stem cells undergoing adipogenic differentiation, showing a measure of chemical lipid saturation composition and an increase in LD accumulation with differentiation (71, 72). While, very interestingly, individual LDs within one adipocyte appear to have an inhomogeneity in their chemical composition, this was not further analyzed.…”
Section: Discussionmentioning
confidence: 99%